2018
DOI: 10.3389/fmicb.2018.01065
|View full text |Cite
|
Sign up to set email alerts
|

High Shedding Potential and Significant Individual Heterogeneity in Naturally-Infected Alpine ibex (Capra ibex) With Brucella melitensis

Abstract: Wildlife reservoirs of infectious diseases raise major management issues. In Europe, brucellosis has been eradicated in domestic ruminants from most countries and wild ruminants have not been considered important reservoirs so far. However, a high prevalence of Brucella melitensis infection has been recently identified in a French population of Alpine ibex (Capra ibex), after the emergence of brucellosis was confirmed in a dairy cattle farm and two human cases. This situation raised the need to identify the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 51 publications
1
20
0
5
Order By: Relevance
“…Infections were first identified in sable bulls in both Outbreak 2 and 3; they were the index cases, the putative source of infection brought for the ranches, with B. melitensis also being isolated from the testes of bulls in Outbreak 3. This is consistent with the potential venereal transmission, as has been reported in the Alpine ibex [ 48 ]. The Bovine Brucellosis Manual of South Africa stipulates that “should semen from an infected sable bull be used for artificial insemination, the risk of spread of the disease is great, but if used for natural service sable bulls do not appear to play a role in the spread of the disease” [ 11 ].…”
Section: Discussionsupporting
confidence: 92%
“…Infections were first identified in sable bulls in both Outbreak 2 and 3; they were the index cases, the putative source of infection brought for the ranches, with B. melitensis also being isolated from the testes of bulls in Outbreak 3. This is consistent with the potential venereal transmission, as has been reported in the Alpine ibex [ 48 ]. The Bovine Brucellosis Manual of South Africa stipulates that “should semen from an infected sable bull be used for artificial insemination, the risk of spread of the disease is great, but if used for natural service sable bulls do not appear to play a role in the spread of the disease” [ 11 ].…”
Section: Discussionsupporting
confidence: 92%
“…No major hyperthermia, polypnea, tachycardia, prostration, anorexia, weight loss or complaints were observed in the animals. Furthermore, in both live animals and at autopsy, no gross lesions suggestive of brucellosis infection (such as described by Freycon et al and Lambert et al [46, 47]) were observed in vaccinated or contact animals, particularly in the genitalia, udder or joints. No loss of appetite or body condition, trauma, or aggressive behavior were observed, despite close contact between individuals of the same batch over an extended period of 3 months.…”
Section: Resultsmentioning
confidence: 74%
“…Here, we studied the genetic and immunogenetic characteristics of 262 ibex captured between 2012 and 2017 by the French Hunting and Wildlife Agency in accordance with legal and ethical regulations (French environmental code, 2005, 2006; Préfecture de Paris, 2009; Préfecture de la Haute-Savoie, 2013, 2015a,b; French Minister of Ecology Sustainable Development and Energy, 2014). Animals were captured by dart-gun xylazine-ketamine anesthesia (Rompun ® , Bayer, Leverkusen, Germany and Imalgène ® , Merial, Lyon, France; 100 mg/individual) following protocols described in Lambert et al 67 . During captures, test-and-cull was implemented on the basis of serological tests (see below for further details on the serological method) as part of management measures decided by the French Authorities (Hars et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Further details on the validation method and the congruence of the FLIA with reference tests (Rose Bengal Test, Complement Fixation Test, iELISA) were provided in Anses (2014). Seropositive ibex were considered as infected by B. melitensis, but not necessarily infectious at the time of capture 67 .…”
Section: Methodsmentioning
confidence: 99%